COMMUNICATION IN RELIGION DIFFERENCES ACCORDING TO THE GUIDE OF THE QUR'AN AND HADITH - Saeful Rokhman (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
Research purposes: To know communication in religious differences according to the guidance of the Qur'an and Hadith. Methods: Qualitative. Result: Based on the guidance of the Qur'an and Hadith, it can be concluded that communication with people of different religions includes: first; not carry out religious coercion, second; do not denounce the gods of other religions, third; to me my religion to you your religion, fourth; do good to followers of other religions, fifth; do good and do justice, and sixth; do not oppress followers of other religions